FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN PEMERIKSAAN KEHAMILAN PADA IBU YANG MEMPUNYAI BAYI DI KELURAHAN BINJAI KECAMATAN MEDAN DENAI TAHUN 2014 - vicky arfeni warongan; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Maternal mortality is till a major problem faced by developing countries. Regular antenatal care can decrease the disability and death of mother and fetus. Based on data from Binjai Village Public Health Center, the scope of K1 reached 47.68% dan 44.66% for the scope of K4 in 2013; the scope of K1 reached 93.2% and 89.6% for the scope of K4 in 2014. The data had not reached the national target of 95%. This study is aimed to analyze the factors related to the completeness of antenatal care among mothers who have infants in Binjai Village, Medan Denai in 2014. This study is analytic with cross sectional design. The population are all mothers who have infants. The samples are 128 mothers. As the results of research, the proportion of incomplete antenatal care reached 18.8% and 81.2% for the complete one. The results of bivariate aanalysis showed that there were seven variables that were not statistically associated with the completeness of antenatal care. They were age (p=0,564), mothers’s education (p=1.000), mother’s occupation (p=1.000), parity (p=0,192), mother’s knowledge (p=0.079), family’s support (p=0,156) and the affordability (p=0.103). Multivariate analysis resulted the equation Y= 1.142 X = 0.631. X was mother’s knowledge and Y was the completeness of antenatal care. It is expected for the staffs of Binjai Village Public Health Center to increase the conseling about how important the antenatal care is which is aimed to improve knowledge women and families. This can be done through cooperation with various parties such as the organization of society, information and communication agencies to be able to provide information about the importance of good antenatal care for the health of t both mother and fetus with a variety of media such as leaflets, CDs, social media and others. The other researchers are expected to be able to continue this research in the different places to find out which factors were significantly associated with the complete antenatal care.